Analisis Penilaian Kinerja Keuangan Perusahaan Dengan Menggunakan Metode Economic Value Added - Rosiana, Rosiana; Iskandar, Iskandar; br Ginting, Yoremia Lestari (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2020)
The aim of this study is to find out how the assessment of financial performance of Unggul Indah Cahaya, Tbk when using the economic value added method. The research method used is descriptive research by analyzing financial statements in the form of balance sheets and incone statements of PT Unggul Indah Cahaya, Tbk, which are listed on the Indonesian Stock Exchange. Based on the results of the analysis and discussion conducted, the result of the value of EVA is fluctuating, whereas 2013, 2014, and 2015 EVA are positive, otherwise at 2016 and 2017 EVA is negative. Theoretically, this research is useful as a contribution of thought for economics, especially financial accounting in the trade industry and chemicals. And is expected to be used as input material, infomation and consideration for the chemical and trade industry in decision making, besides, the results of this study are to expected abauot economic value added to investors and potential investors who will in the PT Unggul Indah Cahaya, Tbk.